Types of oppositions in Malaysian preschoolers' arguments / Angelina Lau - Lau, Angelina (2015)
Most children interact with their peers during their preschool years and within these interactions, there are arguments. Among the work carried out on children’s arguments, Cobb-Moore et al. (2008) and Goodwin and Goodwin (1987), have mentioned that children’s arguments are often perceived as being unproductive and negative by adults. To date, there is also little research done with equally little attention given to such arguments. Developmental theorists (Piaget, 1932, 1959; Vygotsky, 1978) have mentioned that arguments can develop children’s growth cognitively, socially and linguistically. With that in mind and with the lack of research done, it is thus important to look at how Malaysian children, in their formative years, argue among themselves. This study examined arguments that have occurred naturally among sixteen Malaysian preschoolers during their interactions with one another at a preschool cum day care centre. Specifically, it looked at the types of oppositions they used and in what linguistic forms these oppositions have emerged. A qualitative research design was adopted and data was obtained through observations and audio video recording sessions of these 16 preschoolers interacting among themselves. The data was then transcribed, coded and categorized according to the coding schemes of Eisenberg and Garvey (1981) and Brenneis and Lein (1977). Analysis has found that Reason was the dominant type of opposition used but it was also interspersed with other types of oppositions such as Threat, Insistence and Challenge, among others. It was further found that preschoolers’ arguments could be composed of both simple and complex language. Overall, preschoolers’ arguments could be said to be logical, persuasive and coherent. This study, although small and with limitations, may be able to illustrate that Malaysian children in their formative years show signs of being competent arguers and they are also capable of holding themselves in conversations.